The new records of alien species of the genus Euphorbia L. in the south of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Euphorbia davidii Subils (=Euphorbia dentata Michx) and Euphorbia maculata L. are alien species of North American origin that were first discovered in Ukraine in the late twentieth century and are known from a few locations. In recent years, we have identified several new locations of these plants in southern Ukraine. Euphorbia davidii was found in 2 locations: city of Oleshky, Kherson Region (scrap metal base) and the outskirts of the village Prohresivka of Berezanka district of Mykolaiv Region (sunflower field). For the Mykolaiv Region E. davidii is resulted by us for the first time. All previously known localities of E. davidii in Ukraine are confined to railways and ports, probably, the primary centers of plant invasion. The localities identified by us are quite distant from the primary foci of invasion, which indicates the spread of E. davidii beyond their borders on the territory of Ukraine within the secondary range. A number of new E. davidii sites discovered in recent years on railways in different parts of Ukraine and the appearance of the species outside the primary foci of invasion indicate a tendency to naturalize the plant in Ukraine. Euphorbia maculata was found in 7 localities in Kherson (Kherson and environs, Skadovsk, Oleshky) and Dnipropetrovsk (Kryvyi Rig) Regions. For the Kherson Region E. maculata is given by us for the first time. A significant number of new locations, including outside the primary foci of invasion, the high number of individuals in them, indicates a high successful naturalization. At least in the Kherson Region E. maculata is an epecophyte. In addition, in 2019, E. maculata was found by us in Azerbaijan (Baku), where it is very rare. The further spread of E. davidii and E. maculata in Ukraine can be predicted with a high probability.
Keywords: Euphorbia davidii, Euphorbia maculata, alien species, distribution, south of Ukraine.